Analisis Pelaksanaan Penilaian Autentik Di SMA Negeri 1 Waigete - Magdalena Mance; Dian Ernaningsih; Sitti Arafah Bahruddin (PT. ALHAFI BERKAH INDONESIA, 2023)
This study aims to determine the implementation of authentic assessment at SMA Negeri 1 Waigete. This research was conducted for one month from 12 January to 12 February 2023. The research method used was descriptive qualitative. Data collection was carried out using questionnaires, interviews and documentation. Sources of data used in this study are primary data and secondary data. The research results obtained by the researchers indicate that all teachers have carried out authentic assessments. Teachers have used authentic assessment during the learning process which includes three aspects of competency, namely attitudes, knowledge, and skills, but there are still some teachers who do not understand authentic assessment. This is because there are still some teachers who have never attended training, there are many assessment indicators that require a lot of time, and the facilities and infrastructure are inadequate.